(untitled) (Sahel Journal of Life Sciences FUDMA, 2025)
Fertility assessment in turkey toms is important for optimizing reproductive efficiency, especially in commercial breeding programs.Â To optimize reproductive efficiency in turkey breeding, we developed and validated a fertility index for turkey toms using semen parameters, with sperm penetration holes as the response variable. Semen samples from 100 toms were analyzed for six parameters, revealing sperm mobility index (r = 0.864) and progressive motility (r = 0.851) as the strongest predictors of fertility. A simplified linear regression model (RÂ² = 0.851) using semen volume, sperm concentration, and sperm mobility index was selected to create the Turkey Tom Fertility Index. The scaled 0-100 index demonstrated 77.0% overall classification accuracy and 86.7% test set accuracy. This practical tool offers a standardized method for predicting fertility potential, enabling improved breeding efficiency and reproductive outcomes in commercial turkey production.